A Cartel in the Public Interest: NCAA Broadcast Policy During the Early Cold War - Montez de Oca, Jeffrey (American Studies, 2010)
This article explores the intersection of politics, economics, and culture through a study of the National Collegiate Athletic Association's television broadcast policy. The establishment of broadcast regulations in the 1950s transformed the NCAA from a confederation of semi-autonomous institutions into a powerful governing and policing body. Broadcast regulations further transformed the NCAA into a cartel that fixed the value of football broadcasts by limiting supply in order to gain monopoly profits. Claiming the regulations served the public interest shielded them from a possible U.S. Supreme Court “rule of reason” test. This article finds the NCAA's regulation of the television broadcast market and its process of cartelization was supported by the economic conditions of the television age and the cultural conditions of the early Cold War that made the claim that young men's bodies were in need of athletic intervention funded by college football appear reasonable.